Acute Effect of Black Bean (Phaseolus vulgaris L.) Hydrolyzed Protein on Glucose Levels in Adults with Prediabetes and Normal Glucose Tolerance - Ramos-Lopez, Andrea; Mojica, Luis; Gomez-Ojeda, Armando; Macias-Cervantes, Maciste; Luevano-Contreras, Claudia (Current developments in nutrition, 2020)
In silico, biochemical, in vitro, and in vivo assays have shown that black bean hydrolyzed protein (HPF) could decrease glucose absorption by inhibiting digestive enzymes and blocking gastrointestinal transporters. Therefore, the objective was to evaluate the acute effect of different doses of HPF on glucose levels in adults with normal glucose tolerance (NGT) and with prediabetes. A double-blind, placebo-controlled, randomized clinical trial was conducted on 31 adults with NGT and 24 adults with prediabetes. Participants were 25–50-year-old and with a body mass index (BMI) between 25–34.9 kg/m2. After consent, participants were randomized into four groups, placebo or the corresponding HPF (powder) treatment (D1:2.5 g, D2:3.7 g, D3:5 g). Subjects received the placebo, 120 mL of a commercial beverage (Be-light), or the corresponding HPF dose dissolved in 120 mL of Be-light. An oral glucose tolerance test (OGTT) (75 g glucose) was used to measure glucose tolerance before treatment (initial). A second OGTT was used to evaluate the acute effect of the HPF, and blood samples were collected at 0, 60, 120, and 150 min, and blood glucose levels were measured. Data were analyzed using a one-way ANOVA and paired Student’s t-test. Participants with NGT: the D3 group showed a decrease in blood glucose area under the curve (AUC) when compared with the D1 group (13,639.2 ± 1585.9 vs. 16,756.6 ± 2709 mg · min/dL; P = 0.05). However, there was no difference with the placebo group (14,073.7 ± 1825.9 mg · min/dL, P = 0.9). When comparing the initial AUC vs. treatment AUC, the placebo, D2, and D3 groups decreased significantly (P = 0.01). Participants with prediabetes: the D3 group also show a significantly decreased in AUC when compared with the D2 group (19,815 ± 3153 vs. 27,545 ± 5398 mg · min/dL; P = 0.01). However, there was no difference with the placebo group (21,743.5 ± 4503 mg · min/dL, P = 0.8). Additionally, when comparing initial AUC vs. treatment AUC, only the D3 group decreased significantly (P = 0.01). The comparison of the acute effect of three different doses of HPF showed a decrease in blood glucose (AUC) in a dose-dependent manner in participants with prediabetes. CONACYT Problemas Nacionales 2016-2081.